Heat‐killed Staphylococcus aureus reduces atherosclerosis by inducing anti‐inflammatory macrophages. (23rd February 2016) - Frodermann, V.; van Duijn, J.; van Puijvelde, G. H. M.; van Santbrink, P. J.; Lagraauw, H. M.; de Vries, M. R.; Quax, P. H. A.; Bot, I.; Foks, A. C.; de Jager, S. C. A.; Kuiper, J.
Abstract: Background: Staphylococcus aureus cell wall components can induce IL‐10 responses by immune cells, which may be atheroprotective. Therefore, in this study, we investigated whether heat‐killed S. aureus (HK‐SA) could inhibit the development of atherosclerosis. Methods: Atherosclerosis‐susceptible LDL receptor‐deficient mice were administered intraperitoneal HK‐SA twice weekly and fed a Western‐type diet for 6 weeks. Results: HK‐SA administration resulted in a 1.6‐fold increase in IL‐10 production by peritoneal macrophages and splenocytes, and a 12‐fold increase in serum IL‐10 levels. Moreover, aortic plaque ICAM‐1, VCAM‐1 and CCL2 expression levels were significantly downregulated by on average 40%. HK‐SA‐treated mice had reduced numbers of inflammatory Ly‐6C hi monocytes as well as Th1 and Th17 cells in the circulation and spleen, respectively. Attenuated leucocyte recruitment resulted in a significant inhibition of macrophage and T cell infiltration in atherosclerotic plaques, culminating in a significant 34% reduction in the development of atherosclerosis. To determine the effects of intraperitoneal HK‐SA treatment, we stimulated macrophages with HK‐SA in vitro . This resulted in a significant toll‐like receptor 2 (TLR2)‐dependent increase in IL‐10, arginase‐1, iNOS, TNF‐ α, PD‐L1, CCL22 and indoleamine 2, 3‐dioxygenase expression. It was found that phosphoinositide 3‐kinase crucially determined the balance of pro‐ and anti‐inflammatory gene expression. The HK‐SA‐induced macrophage phenotype resembled M2b‐like immunoregulatory macrophages. Conclusions: We have shown that HK‐SA treatment induces strong anti‐inflammatory IL‐10 responses by macrophages, which are largely dependent on TLR2 and PI3K, and protects against the development of atherosclerosis. Commensalism with S. aureus could thus reduce cardiovascular events.